THE ROLE OF THE MA KAUMAN PADANG PANJANG IN PRINTING THE MUHAMMADIYAH ASSOCIATION CADRE IN PABASKO - irwansyah irwansyah (Program Pascasarjana UMSB, 2022)
This research was conducted entitled The Role of The MA KMM Kauman Padang Panjang in printing the Muhammadiyah Organization cadres in Pabasko. This research was conducted with the formulation of the problem 1. Efforts of MA KMM Kauman Padang Panjang in printing organizational cadres 2. Efforts of MA KMM Kauman Padang Panjang in printing community cadres 3. Efforts of MA KMM Kauman Padang Panjang in producing national cadres. This research was conducted in order to address the perceived shortage of cadres in the Padang Panjang area of ​​Batipuh X Koto. By conducting this research, the writer was able to know the role of MA KMM Kauman Padang Panjang in producing Persarikatan Muhammadiyah cadres, Ummat cadres and Nation cadres in MA KMM Kauman Padang Panjang.This research was conducted by field research method (Field Research) and is descriptive qualitative by conducting observations and interviews as data collection methods. As for the analysis and techniques for testing the validity of the data, it is done by grouping, presenting and drawing conclusions from the data obtained, then triangulation will be carried out for the validity and accuracy of the data obtained.Muhammadiyah business charity is a forum or a means to print and develop Muhammadiyah cadres which will then be transformed into organizational cadres, ummah cadres and national cadres. Those who have competencies and main characters as characteristics of their cadres.The result of this research is that MA KMM Kauman Padang Panjang has made various efforts in producing and producing cadres of the organization, the ummah and the nation. MA KMM Kauman Padang Panjang. as the charity of Muhammadiyah MA KMM Kauman Padang Panjang always makes innovation efforts to realize the target as a cadre school in the Muhammadiyah charity business environment. To achieve this goal, it is deemed necessary to have cooperation and collaboration between the leaders of the association and the leaders of business charities. In addition, as a business charity that focuses on preparing the younger generation of Muhammadiyah, MA KMM Kauman Padang Panjang should actually make the values ​​championed by Muhammadiyah be internalized and inspired by all its teaching staff.